Teaching Idioms through Drilling Technique in IELTS Academic Speaking Preparation Class - Kadiatmaja, Agung Pranoto (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This research aimed to investigate the effectiveness of drilling technique in enhancing takers’ comprehension of idioms within the context of IELTS academic speaking preparation. The research was conducted at Mushlih Institute's English Development Centre in Surabaya and involved 40 takers enrolled in an IELTS Academic Speaking Preparation class for international undergraduate programs. The quantitative method was used in conducting this research which was focused on a quasi-experimental design. Takers were chosen as the experimental group's sample, and six takers were chosen as the control group. Cluster random sampling was used to collect the sample. The data was analyzed using parametric statistics in the research. Normality and homogeneity tests are prerequisites for parametric statistics to recognize the substantial effectiveness of teaching idioms to improve takers' IELTS speaking proficiency. The results indicate that drilling technique significantly improves takers' ability to understand and apply idioms in IELTS speaking Preparation Class. The independent samples t-test showed a significant result (p = 0.000), indicating that teaching idioms using the drilling technique has a meaningful positive effect on takers' IELTS speaking skills at the English Development Center of the Mushlih Institute.